Genome-wide association study (GWAS) uncovers candidate genes linked to the germination performance of bread wheat (Triticum aestivum L.) under salt stress - Saeideh Javid; Mohammad Reza Bihamta; Mansour Omidi; Ali Reza Abbasi; Hadi Alipour; Pär K. Ingvarsson; Peter Poczai (BMC Genomics)
Abstract Background Improving the germination performance of bread wheat is an important breeding target in many wheat-growing countries where seedlings are often established in soils with high salinity levels. This study sought to characterize the molecular mechanisms underlying germination performance in salt-stressed wheat. To achieve this goal, a genome-wide association study (GWAS) was performed on 292 Iranian bread wheat accessions, including 202 landraces and 90 cultivars. Results A total of 10 and 15 functional marker-trait associations (MTAs) were detected under moderate (60 mM NaCl) and severe (120 mM NaCl) salinity, respectively. From genomic annotation, 17 candidate genes were identified that were functionally annotated to be involved in the germination performance of salt-stressed wheat, such as CHX2, PK2, PUBs, and NTP10. Most of these genes play key roles in DNA/RNA/ATP/protein binding, transferase activity, transportation, phosphorylation, or ubiquitination and some harbored unknown functions that collectively may respond to salinity as a complex network. Conclusion These findings, including the candidate genes, respective pathways, marker-trait associations (MTAs), and in-depth phenotyping of wheat accessions, improve knowledge of the mechanisms responsible for better germination performance of wheat seedlings under salinity conditions.